WinLight: a WiFi-based occupancy-driven lighting control system for smart building - Zou, Han (2020)
Artificial lighting accounts for a significant proportion (19%) of energy consumption in building environments. This large contribution calls for the creation of energy-efficient lighting control schemes. In this article, we present WinLight, a novel occupancy-driven lighting control system that aims to reduce energy consumption while simultaneously preserving the lighting comfort of occupants. By leveraging the fine-grained occupancy information estimated by existing WiFi infrastructure in a non-intrusive manner, WinLight computes an appropriate dimming command for each lamp based on a novel lighting control algorithm. A centralized lighting control system assigns these commands to a zonal gateway, and occupancy-driven lighting control is achieved by actuating the brightness adjustment with a local controller integrated within each lamp. Moreover, a WinLight App is designed to enable occupants to customize their luminance preferences and to control nearby lamps using their mobile devices. We implemented WinLight in a 1500 m2 multi-functional office in Singapore and conducted an experiment during 24 weeks. The experimental results demonstrate that WinLight achieves 93.09% and 80.27% energy savings compared to static scheduling lighting control scheme and PIR sensor based lighting control scheme while guaranteeing the personalized lighting comfort of each occupant.